Perceiving determinant of happiness among special educators / Nur Fadhilah Azmi, Siti Norfatihah Rahim and Wan Nur Ain Natasha Wan Bdrulhisham - Azmi, Nur Fadhilah; Rahim, Siti Norfatihah; Wan Bdrulhisham, Wan Nur Ain Natasha (2019)
Happiness is the major concept in the mental health including positive emotions such as great pleasure, calmness and a sense of involvement. However, there are many factors that can affect happiness in daily life such as income, marital status, age and workload. The aim of this study was to identify perceived factors of happiness among special educators from northern region of Peninsular Malaysia. There are four major factors that considered in this study which is workload, health condition, level of education and total income as well as demographics factors. The instrument was adapted from Oxford Happiness Questionnaire (OHQ), disseminated to the selected 123 special educators from secondary schools. The main statistical analysis, Multiple Linear Regression was used with the combination of basic statistics. The result indicated that most of the special educators are happy with their current work. The finding deliberated, burden (/J= -4.3./8) and workload (IJ= -3. 085) emerged as reliable predictors of stress among the special educators (p-va/ue<O. OS).